Scaling LCAS-APT in Asia - Urfels, Anton; Varkey, Lisa Mariam; Vettil, Prakashan; Koirala, Ashish; Nayak, Hari Sankar; Santos, Rosette; Quicho, Emma; Samaddar, Arindam; Flor, Rica Joy (International Rice Research Institute, 2025)
The Landscape-Scale Crop Assessment System for Agronomic Partnership and Technology (LCAS–APT) is a streamlined, field-based data system developed to pinpoint areas where agronomic investments can most effectively boost productivity, resilience, and farmer income. By combining spatial diagnostics, household-level observations, and data on management practices, LCAS–APT offers a systematic approach to identifying constraints, benchmarking present performance, and prioritizing solutions tailored to specific farming systems. These data-driven insights directly inform the design and improvement of Minimum Viable Products (MVPs) within the Agronomy Partnership Platform (PAAS). This approach ensures that new tools and interventions are crafted to address actual, system-level challenges rather than relying on broad assumptions. The brief below highlights initial findings from recent LCAS–APT data collection campaigns across Asia, demonstrating how the system facilitates more precise, evidence-based agronomic innovation. In particular, it presents insights and evidence from India, the Philippines, and Cambodia.